(untitled) (Medico Legal Update, 2020)
Matoa (Pometia Pinnata) is a typical Papua fruit plant, classified as a large tree with an average height of 18 meters with a maximum average diameter of 100 cm. Generally bear fruit once a year, flowering in July to October and fruiting 3 or 4 months later. Some research shows that the leaves, fruit bark and matoa tree bark contain tannins, saponins and alkaloids. The purpose of this study was to produce a formulation and test the effectiveness of a cream extract of matoa tree bark (pometia pinnata) honey combination on staphylacoccus aureus bacteria. This research is a purely experimental research to produce an extract of the matoa tree bark cream and then test its effectiveness in the treatment of staphylococcus aureus bacteria, with a completely randomized design (CRD) design. The results showed that the matoa rind extract cream was effective against staphylacoccus aureus bacteria with a significant value of 0.00 <0.005. This study recommends a combination of honey bark stem extract cream for the treatment of staphylococcus aureus bacterial infections.